Paediatric urachal benign teratoma: a case report and review of the literature. Issue 9 (30th January 2014) - Kingo, Pernille Skjold; Høyer, Søren; Marinovskij, Edvard; Rawashdeh, Yazan Faiz
<x xml:space="preserve">Abstract</x> Urachal anomalies are most often seen in children, seldom in adults, but are in general considered rare. The estimated incidence is one in 5000–7000 live births and appears twice as common in males. Despite their rarity, they need to be considered by clinicians, as diseases in the urachus can mimic many abdominal and pelvic conditions and constitute an important differential diagnosis to these. Diagnosis can be made by clinical examination and imaging modalities (computed tomography, ultrasonography, magnetic resonance imaging, voiding cystourethrogram), but some are discovered incidentally. Management of symptomatic urachal anomalies is surgery. Histological examination of the specimen should always be performed to rule out malignancy. We report on the first adolescent described in the literature diagnosed with a urachal sinus harboring a benign teratoma. A combination of the two pathologies is by inference an extremely rare condition, which we here report on and we review the relevant literature on this topic.